Regional strain score as prognostic marker of cardiovascular events. from the Multi-Ethnic Study of Atherosclerosis (MESA). (3rd October 2022) - Pezel, T; Bluemke, D; Wu, C; Lima, J; Ambale Venkatesh, B
Abstract: Background: Left ventricular (LV) circumferential strain (Ecc) is an accurate indicator of regional myocardial function, particularly using the regional Ecc or layer-specific strain. Purpose: To investigate the prognostic value of a regional strain score (RSS) for predicting the incident of heart failure (HF) and coronary heart disease (CHD) in a population without a history of cardiovascular disease at baseline. Methods: In Multi-Ethnic Study of Atherosclerosis (MESA), 1, 506 study participants (63.3±9.4 years, 54.6% men) underwent tagged magnetic resonance imaging for left ventricular circumferential strain (Ecc) analysis. Using −17% and −10% as Ecc cut-offs, each segment was rated from 0–2 points according to the Ecc value of each layer. The endo-Ecc, mid-Ecc, and epi-Ecc values from the 16-segment model were used to calculate three RSS: Endo-, Mid-, and Epi-RSS, respectively, which were defined as a percentage of good LV regional function. The Intramyocardial-RSS was the sum of these three RSS. Cox proportional models were used to evaluate the association between RSS and cardiovascular outcomes. Results: After a median [IQR] follow-up of 15.9 [12.9–16.6] years, 122 hard CHD and 91 HF were observed. After adjustment, Mid-, Epi-, and Intramyocardial-RSS values <50% were independently associated with HF (HR 1.43; 95% CI [1.08–2.87], p=0.004; HR 1.80; 95% CI [1.12–3.07], p<0.001; and HR 2.01; 95% CI [1.19–3.20], p<0.001). After adjustment, Endo-, Mid-, Epi-, and Intramyocardial-RSS <50% were also independently associated with hard CHD (HR 1.31; 95% CI [1.03–1.51], p=0.04; HR 1.79; 95% CI [1.26–2.57], p<0.001; HR 2.03; 95% CI [1.45–3.40], p<0.001; and HR 2.28; 95% CI [1.51–3.53], p<0.001). Conclusion: Layer-specific regional Ecc, assessed by RSS, provides a robust, independent predictive value for incident HF and hard CHD in asymptomatic participants without any cardiovascular disease at baseline. Funding Acknowledgement: Type of funding sources: None.